Pelatihan Pembuatan Kuliner Kekinian Takoyaki pada Ibu-Ibu PKK Desa Kaligading, Kec. Boja, Kab. Kendal - Rowiyani Rowiyani; Mukhlidin Mukhlidin; Alfin Muslikhun; Khoirul Sholeh; Iqbal Maulana; Wanda Pratiwi (Fakultas Teknik Universitas Cenderawasih, 2023)
Viral culinary delights are always sought after by the public especially teenagers. Takoyaki is a culinary from Japan that is quite viral among the public and is favored by the public. among the public and is favored by the public. Training on making takoyaki training for Family Empowerment and Welfare (PKK) in Kaligading village aims to increase creativity and independence. In addition, Family Empowerment and Welfare (PKK) can also open a business selling takoyaki with variants of toppings so as to increase family income. variants of toppings so as to increase family income. Making takoyaki is also quite easy and does not require a long time so it is very suitable for business and family celebrations. business or family celebration. The results of this service activity are expected to expected to be able to increase the creativity and income of Family Empowerment and Welfare (PKK) by establishing takoyaki home culinary business. Variants of toppings used in takoyaki also varies. In addition, Family Empowerment and Welfare (PKK) can also serve for family dishes when there is a celebration of family meals when there is a celebration of recitation, family gatherings, and others.